Translator’s creative nature: a cognitive model of formalization - Diomidova, Alla (Kalbotyra, 2007)
The intention of this study is to propose a new approach to the analysis of literary translation. It is assumed that the qualitative differences between Goethe’s Faust and Pasternak’s interpretation of Faust are determined by different conceptual systems of the author and the translator. The aim of this study is to describe Pasternak’s conceptual system that is reflected in the text of Faust translation. Goethe‘s conceptual system, as reflected in his Faust, is based on two conceptual metaphors: WELLNESS IS WATER and WELLBEING IS FOOD. These metaphors are grounded in body experience – CONTAINER image-schema. Pasternak’s conceptual system, reflected in his Faust, is based on different from Goethe’s conceptual metaphors: FEELINGS ARE ILLNESS and FEELINGS ARE ACTIONS OF NATURE. These metaphors reflect Pasternak’s view of existence: a universe-sized entity, not involving any ‘inner’ dimension, or duality. Because of his own understanding of Faust, Pasternak omits or moderates references to action or activity, including activity of nature.